REVIEW METODOLOGI PENELITIAN DALAM PENGEMBANGAN MODEL INQUIRY UNTUK PENDIDIKAN - Fadillah, Muhammad Aizri; Tanjung, Yul Ifda; Usmeldi, Usmeldi; Lufri, Lufri; Festiyed, Festiyed; Mawardi, Mawardi (Jurnal Muara Pendidikan, 2025)
Inquiry-based learning (IBL) has been proven to be an effective approach to developing 21st-century skills, such as critical thinking, collaboration, and creativity. However, the adaptation of inquiry phases to different levels of education and specific learning objectives remains a challenge that has not been thoroughly answered. This study used a systematic literature review (SLR) approach to review the IBL model with a focus on identifying the phases of inquiry, exploring the adaptation of IBL at various levels of education, analyzing relevance to learning objectives, and evaluating the effectiveness of scaffolding and research design. From an analysis of 2018-2024 taken from the Google Scholar database, it was found that IBL consists of five main phases-orientation, problem formulation, exploration, elaboration, and evaluation effectiveness depending on the educational context and level of scaffolding. For example, the 5E-Based Inquiry model strongly supports science learning in elementary school, while the self-investigation phase is more appropriate in higher education. In addition, scaffolding, such as the use of advanced organizers and digital simulations, was shown to support student engagement during the inquiry process. This research highlights the flexibility and effectiveness of IBL in supporting conceptual understanding, critical thinking skills, and problem-solving and offers insights into the adaptation and implementation of relevant models for different educational needs.